Fire history reconstruction in grassland ecosystems: amount of charcoal reflects local area burned - Leys, Bérangère; Brewer, Simon C.; McConaghy, Scott; Mueller, Joshua; McLauchlan, Kendra K. (My University, 2015)
Fire is one of the most prevalent disturbances in the Earth system, and its past characteristics can be reconstructed using charcoal particles preserved in depositional environments. Although researchers know that fires produce charcoal particles, interpretation of the quantity or composition of charcoal particles in terms of fire source remains poorly understood. In this study, we used a unique four-year dataset of charcoal deposited in traps from a native tallgrass prairie in mid-North America to test which environmental factors were linked to charcoal measurements on three spatial scales. We investigated small and large charcoal particles commonly used as a proxy of fire activity at different spatial scales, and charcoal morphotypes representing different types of fuel. We found that small (125–250 μ m) and large (250 μ m–1 mm) particles of charcoal are well-correlated (Spearman correlation = 0.88) and likely reflect the same spatial scale of fire activity in a system with both herbaceous and woody fuels. There was no significant relationship between charcoal pieces and fire parameters <500 m from the traps. Moreover, local area burned (<5 km distance radius from traps) explained the total charcoal amount, and regional burning (200 km radius distance from traps) explained the ratio of non arboreal to total charcoal (NA/ T ratio). Charcoal variables, including total charcoal count and NA/ T ratio, did not correlate with other fire parameters, vegetation cover, landscape, or climate variables. Thus, in long-term studies that involve fire history reconstructions, total charcoal particles, even of a small size (125–250 μ m), could be an indicator of local area burned. Further studies may determine relationships among amount of charcoal recorded, fire intensity, vegetation cover, and climatic parameters.
Citation: Leys, B., Brewer, S. C., McConaghy, S., Mueller, J., & McLauchlan, K. K. (2015). Fire history reconstruction in grassland ecosystems: amount of charcoal reflects local area burned. Environmental Research Letters, 10(11), 114009. https://doi.org/10.1088/1748-9326/10/11/114009